An Illocutionary Speech Act Analysis in Russian President Vladimir Putin's Political Speeches - Amami Shofiya Al Qorin; Kholisin; Achmad Yani (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
Language has an essential role in human communication within society, and understanding the language requires a pragmatic approach. One of the topics in pragmatics is speech acts, particularly illocutionary acts based on Austin's theory, which can be conveyed in various forms, including political speeches. This research analyzes illocutionary speech act and their functions in the political speeches of Russian President Vladimir Putin. The data collection tools in this research consist of the researchers, the document, and the auxiliary table for analysis as the secondary tool. The technique of data collection is the listening-writing method. As for data analysis techniques, the researcher uses Miles and Huberman's method. It consists of four steps: data collection, data presentation, data identification, and conclusion. The results of this research are that there are five expressions of assertives, and their functions are reporting, informing, claiming, and complaining. And one is commissive, and a function is to promise. and six of the directive verbs and their functions: command, permission, prohibition, guidance, and question. And five of the verbs of expressives and their functions are criticism and admonition, and one of the verbs of declaratives and the function mentioned is acknowledgment. These results highlight how speech acts serve as strategic tools in political discourse to convey intentions, establish authority, and influence the audience.